2022
DOI: 10.3390/machines10080634
|View full text |Cite
|
Sign up to set email alerts
|

Planet Load-Sharing and Phasing

Abstract: This paper presents an analysis of the scientific literature devoted to the problem of load sharing and phasing in planetary gearboxes. The wide range of research topics demonstrates the technical challenges of understanding planetary load-sharing and planet phasing. This review includes studies having the goal of developing models for load sharing and exploring the positive or negative effects of different parameters such as phasing on the load distribution among planets. Practical aspects are also considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 119 publications
0
0
0
Order By: Relevance
“…The helix angle incorporated in the gears of the planetary system contribute to an overall reduced PPTE, which is particularly significant in medical equipment applications [72]. In the case of planetary gearsets, studies have shown that a larger number of planets improve the load sharing conditions since the operation load is distributed to multiple planets [73,74]. However, this conclusion can be supported only by theoretical models since, in reality, a larger number of planets would increase the sensitivity to errors [74].…”
Section: Results Of Optimized Design Solution Contact Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The helix angle incorporated in the gears of the planetary system contribute to an overall reduced PPTE, which is particularly significant in medical equipment applications [72]. In the case of planetary gearsets, studies have shown that a larger number of planets improve the load sharing conditions since the operation load is distributed to multiple planets [73,74]. However, this conclusion can be supported only by theoretical models since, in reality, a larger number of planets would increase the sensitivity to errors [74].…”
Section: Results Of Optimized Design Solution Contact Analysesmentioning
confidence: 99%
“…In the case of planetary gearsets, studies have shown that a larger number of planets improve the load sharing conditions since the operation load is distributed to multiple planets [73,74]. However, this conclusion can be supported only by theoretical models since, in reality, a larger number of planets would increase the sensitivity to errors [74]. In this particular model, since the planets are inseparably attached to the rollers that control the fluid's flow rate, the use of two planets is mandated.…”
Section: Results Of Optimized Design Solution Contact Analysesmentioning
confidence: 99%